THEORETICAL BASIS OF RESEARCH OF TERRITORY TOURIST POTENTIAL - PASIEKA, Stanislava; DZHUMURAT, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The theoretical foundations of the study of the territory tourist potential in the article are developed. The main approaches to the consideration of the potential are determined – resource, factor and dialectical. This made it possible to substantiate the dialectical understanding of tourism potential as a structural economic category that determines the ability of the tourism industry and its subjects to develop based on the use of available and production of new resources, as well as support from authorities (through prioritization and regulatory mechanisms) to achieve optimal results. The optimal results of the development of the tourist potential involve the coordination of economic goals and the goals of sustainable development, which involve the preservation and restoration of natural and historical-architectural monuments, the cultural identity of the local population (ethnic groups, indigenous peoples). The classification of the resource base and components of the territory tourist potential by resource (natural, historical and cultural, emotional potential), business (personnel, innovation, infrastructural, social potential) and administrative (regulatory, financial, economic, institutional, informational, security potential) blocks is proposed. The characteristics of the tourist potential, which determine the peculiarities of its evaluation, are updated. There are such characteristics as factual (localization, accessibility), quantitative (volumes, number, area), qualitative (condition (preservation, conservation, restoration), security), relative (concentration, load), market (capacity, cost, competitive advantages, uniqueness), consequential (development, profitability, tourism specialization of the economy, integration into the international market of tourist services, tourist attractiveness of the destination). The functionality of the tourist potential is determined, which emphasizes its security and protection, economic, integration, social and unifying significance. The obtained results are the basis for the improvement of methodological recommendations for the assessment of tourist potential and their approbation at the level of Ukraine, regions and communities.